MOF-derived MoP nanorods decorated with a N-doped thin carbon layer as a robust lithiophilic and sulfiphilic nanoreactor for high-performance Li–S batteries. Issue 17 (3rd August 2022) - Wang, Xiaoxiao; Meng, Lingshuai; Liu, Xueqiang; Deng, Nanping; Yan, Zirui; Wang, Gang; Wei, Liying; Zhang, Lugang; Cheng, Bowen; Kang, Weimin
Abstract : A MoP@NC/PCNFs-modified Celgard separator was designed for use in lithium–sulfur batteries. Abstract : Lithium–sulfur (Li–S) batteries are severely hindered by low sulfur utilization and short cycling lives, especially at high sulfur loading levels. An effective solution to address these problems is to improve the sulfiphilicity of lithium polysulfides (LiPS) and the lithiophilicity of the lithium anode. However, it is a great challenge to simultaneously optimize both aspects. To solve these problems, herein, a modification strategy involving a functional separator is used, coating a composite including MoP nanorods decorated with a N-doped thin carbon layer (MoP@NC) and porous carbon nanofibers (PCNFs) onto the surface of a Celgard separator. The obtained MoP@NC material, derived from a molybdenum-based MOF (Mo-MOF), possesses abundant porosity and multiple catalytic sites, with uniform and stable rod-shaped morphology. The PCNFs and N-doped thin carbon layer can effectively alleviate volume expansion, buffer the electrolyte, and trap LiPS. When applied as a modification layer coated on the separator, the MoP@NC/PCNFs-based cell with optimized lithiophilicity and sulfiphilicity enables desirable sulfur electrochemistry, including high reversibility of 902.9 mA h g −1 after 400 cycles at 1C and 654.5 mA h g −1 after 500 cycles at 2C. This work provides a novel strategy by which MoP derived from a MOF can be applied in the design of high-performance Li–S batteries.